(untitled) (المجلة الدولية للعلوم المالية والإدارية والاقتصادية, 2025)
This research aimed to examine the impact of ownership structure patterns on investment efficiency through the mediating role of information asymmetry. The study analyzed the annual financial reports of a sample of 14 banks listed on the Iraq Stock Exchange for the period 2014-2023. Manual content analysis of the annual reports was used to extract data for measuring the research variables. The study concluded that institutional ownership plays the most significant role in enhancing investment efficiency, both directly and indirectly, by reducing information asymmetry. This underscores the effectiveness of institutional investors in monitoring management behavior and improving transparency within companies. Conversely, foreign ownership demonstrates a significant negative impact, while ownership concentration and managerial ownership have a minimal effect on investment efficiency, and the information environment does not enhance their effects.